Pengembangan Media Pembelajaran Interaktif Berbasis Articulate Storyline Materi Sistem Reproduksi Manusia Kelas XI SMA Negeri 11 Pangkep - Muhlis Muhlis (UNM Journal of Biological Education, 2022)
This study is a development research that aims to produce a product in the form of interactive learning media based on Articulate Storyline in Human Reproductive System material. This development research refers to the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were students of grade XI. IPA at SMAN 11 Pangkep. Based on the results of data analysis, it shows that 1) the interactive learning media based on Articulate Storyline on Human Reproductive System material meets the valid criteria with a mean score of 4.54 (very valid), 2) the interactive learning media based on Articulate Storyline material on Human Reproductive System material meets the practical criteria based on the results of the teacher's response by 95.93% (very positive) and the results of the student’s response by 84, 56% (very positive), 3) the interactive learning media based on Articulate Storyline on Human Reproductive System material meets the effective criteria with the percentage of completeness of learning outcomes by 84.62%. Based on the results of the study, it can be concluded that the interactive learning media based on Articulate Storyline material on Human Reproductive System material has met the valid, practical, and effective criteria.